Alternaria and Cladosporium calendar of Western Thrace: Relationship with allergic rhinitis symptoms. (15th September 2015) - Katotomichelakis, Michael; Nikolaidis, Christos; Makris, Michael; Proimos, Efklidis; Aggelides, Xenophon; Constantinidis, Theodoros C.; Papadakis, Chariton E.; Danielides, Vassilios
Abstract : Objectives/Hypothesis: Alternaria and Cladosporium are the most important outdoor moulds. The aim of this study was to present fungal spore monitoring data, investigate the relationship of fungal counts with climate conditions, and to explore the clinical significance of Alternaria and Cladosporium species monitoring in allergic rhinitis (AR). Study Design: Analytic observational study. Methods: A 7‐day volumetric trap was used to collect circulating Alternaria and Cladosporium fungi. Sixty‐nine AR patients were studied and recorded their symptoms by Total 5 Symptoms Score (T5SS). Sensitization prevalence to fungi species was detected by skin prick tests. Monitoring data were correlated to climate conditions and patients symptoms score. Results: Alternaria and Cladosporium were detected throughout the calendar year in ranges of 0 to 217 spores/m 3 and 6.5 to 1, 600 spores/m 3 per day, respectively. Highest daily concentrations of both fungi were detected during the summer (73.9 ± 34.4 spores/m 3 for Alternaria and 595.8 ± 288.0 spores/m 3 for Cladosporium ) and lowest during the winter (2.4 ± 3.0 spores/m 3 for Alternaria and 24.3 ± 15.7 spores/m 3 for Cladosporium ). Both were positively correlated to mean daily temperature and negatively to relative humidity (all P < 0.001). Clinically, a strong significant correlation between T5SS and airborne fungi levels, both for Alternaria (r = 0.822, P = 0.001) and Cladosporium (r = 0.787, P = 0.002) species was observed. Conclusions: We found Cladosporium to be the most frequently detected airborne mould, whereas Alternaria was the most prevalent with regard to sensitization rate. Patients' symptoms score was significantly correlated to spore concentrations. Both fungi were clearly affected by climate factors, such as temperature and relative humidity. These findings are important in AR management. Level of Evidence: N/A. Laryngoscope, 126:E51–E56, 2016